2008
DOI: 10.1017/s1368980008001833
|View full text |Cite
|
Sign up to set email alerts
|

Iron status of adolescent girls from two boarding schools in southern Benin

Abstract: Iron deficiency (ID) is the most prevalent micronutrient deficiency in the world, particularly in developing countries. Blood samples and a qualitative FFQ on Feand vitamin C-rich foods were obtained in 180 adolescent girls aged 12 to 17 years living in two boarding schools from south Benin. ID, defined as serum ferritin either ,20 mg/l or 20-50 mg/l, plus two of the following parameters: serum Fe , 11 mmol/l, total iron-binding capacity . 73 mmol/l or transferrin saturation , 20 %, was found in 32 % of subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…Second, about 21 % of households in the study area were reported food insecure since farming, which is the primary means of survival, is limited to the rainy season (5) . Diets are also based predominantly on starchy staples with little or no animal products and few fresh fruits and vegetables (1,2,7) . According to the 2012 Benin DHS, only 28·3 and 33·8 % of children received the minimum diet diversity and minimum acceptable diet, respectively (7) , reflecting the higher rates of poverty and less diverse production portfolios in the study area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, about 21 % of households in the study area were reported food insecure since farming, which is the primary means of survival, is limited to the rainy season (5) . Diets are also based predominantly on starchy staples with little or no animal products and few fresh fruits and vegetables (1,2,7) . According to the 2012 Benin DHS, only 28·3 and 33·8 % of children received the minimum diet diversity and minimum acceptable diet, respectively (7) , reflecting the higher rates of poverty and less diverse production portfolios in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews of dietary intake data from Benin showed that recommended daily intakes of key micronutrients, such as vitamin A and Fe, were not met (1)(2)(3)(4) . At the subnational level, in northern Benin, macronutrient intakes are also too low (5,6) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in Taiwan, most iron deficiency cases in males aged 10 to 18 years were attributed to inadequate food consumption [25]. Alaoèfe et al [27] observed that the majority of girls that presented anemia and iron deficiency had low consumption frequency of meat, poultry, vegetables, and fruits. In the study by Borges et al [26], children and adolescents that consumed low iron bioavailability diets had 1.68 times more likely (95% CI 1.10-2.56) of suffering anemia than those who consumed diets with high bioavailability of the nutrient.…”
Section: Discussionmentioning
confidence: 99%
“…Alaofè et al (3) present findings of a study assessing iron status among a sample of 180 adolescent girls in Benin which found iron deficiency to be a significant health problem in this population. Iron deficiency is also the focus of a paper from El Ati et al (4) exploring the aetiological factors and perception of anaemia in Tunisian women of reproductive age.…”
mentioning
confidence: 99%